Comparative constitutional history. principles, developments, challenges - Biagi, Francesco; Frosini, Justin Orlando; Mazzone, Jason, 1970- (Brill, 2020)
"While comparative constitutional law is a well-established field, less attention has been paid so far to the comparative dimension of constitutional history. The present volume, edited by Francesco Biagi, Justin O. Frosini and Jason Mazzone, aims to address this shortcoming by bringing focus to comparative constitutional history, which holds considerable promise for engaging and innovative work along several key avenues of inquiry. The essays contained in this volume focus on the origins and design of constitutional governments and the sources that have impacted the ways in which constitutional systems began and developed, the evolution of the principle of separation of powers among branches of government, as well as the origins, role and function of constitutional and supreme courts. Contributors include: Mark Somos, Gohar Karapetian, Justin O. Frosini, Viktoriia Lapa, Miguel Manero de Lemos, Francesco Biagi, Ctherine Andrews, Gonçalo de Almeida Ribeiro, Mario Alberto Cajas-Sarria, and Fabian Duessel."
Keywords: Constitutional law.; Constitutional history.; Separation of powers.; Constitutional courts.; Federal government.; Droit constitutionnel.; Histoire constitutionnelle.; Séparation des pouvoirs.; Cours constitutionnelles.; Constitutional courts; Constitutional history; Constitutional law; Federal government; Separation of powers